Engagement in healthcare decision-making and associated factors among patients with chronic non-communicable diseases in Southwest Ethiopia, 2023 - Sadik Abdulwehab; Yeshitila Belay; Frezer Kedir; Ebrahim Yimam; Admasu Belay (Clinical Epidemiology and Global Health)
Background: Chronic Non-communicable diseases require lifelong care involving patients, families, a team of their care providers, and significant others. Additionally, engaging patients in their healthcare decision-making is crucial for achieving better clinical outcomes. This study aimed to assess patients' engagement in healthcare decision-making and associated factors among adults with chronic non-communicable diseases in Southwest Ethiopia. Methods: A cross-sectional study design was used among 422 participants at the public hospital of Jimma town. Study participants were consecutively recruited from May 01 to June 01, 2023. A structured Patient Activation Measure was used to measure patient engagement in healthcare decision-making. Descriptive statistics and binary logistic regression analysis describe the association between dependent and independent variables. Result: A total of 422 patients with chronic diseases participated in the study yielding a response rate of 99.3 %. Slightly greater than one-third (35.8 % (95 % CI: 31.19, 40.41)) of participants in The study area had a high engagement in healthcare decision-making. Residence (Odd ratio 0.27; 95 % confidence interval 0.137–0.534), educational level(Odd ratio 0.168; 95 % confidence interval 0.064–0.443), access to information materials(Odd ratio 0.226; 95 % confidence interval 0.112–0.458), duration(Odd ratio 3.864; 95 % confidence interval 2.083–7.169), health literacy(Odd ratio 1.192; 95 % confidence interval 1.111–1.28), and preference for autonomy(Odd ratio 1.097; 95 % confidence interval 1.058–1.136) were factors statistically associated with patient engagement in healthcare decision-making. Conclusion: One-third of study participants reported high engagement in healthcare decision-making. Thus, healthcare providers should pay attention to patients with low educational levels, who do not have access to information materials, low health literacy levels, and their preference for autonomy to engage them in their healthcare decision-making.